Password Control Multi Line Circuit Breaker Using IoT - Nandakumar, G; Praveenkumar, B; Selvakumar, K; Sarojini, L (International Journal of Computer Sciences and Engineering, 2018)
Security is the prime disquiet in our everyday life while playing out any action. In the present situation, inadvertent demise of lineman is regularly perused and prove. Toward this path, a wellbeing measure to safe watch the administrator is discovered extremely essential investigating the present working style. The electric lineman security framework is intended to control the control board entryways and electrical switch by utilizing a secret word for the wellbeing. Basic electrical mishaps to lineman are on the ascent amid electric line fix might be because of absence of correspondence and co-appointment between the support staff and electric substation staff. The proposed framework gives an answer that guarantees wellbeing of lineman. In this proposed system the control (ON/OFF) of the electrical lines lies with line man in IOT. This project is arranged in such a way that maintenance staff or line man has to enter the password in mobile or webpage to ON/OFF the electrical line. Now if there is any fault in electrical line then line man will switch off the power supply to the line by entering password and comfortably repair the electrical line, and after coming to the substation line man switch on the supply to the particular line by entering the password.